PERAN MEDIA SOSIAL DAN KREDIBILITAS MICRO-INFLUENCER TERHADAP NIAT BERKUNJUNG WISATAWAN KE DESTINASI NAPABHALE - Muhammad Suriyadarman Rianse (Kepariwisataan: Jurnal Ilmiah, 2025)
This study examines the influence of social media and micro-influencer credibility on tourist visit intention to the Napabhale tourism destination, with destination awareness as a mediating variable. As digital platforms increasingly shape travel decisions, understanding how content and influencer trustworthiness affect tourist behavior is essential. This quantitative research employs Structural Equation Modeling-Partial Least Squares (SEM-PLS) to analyze data collected from 150 respondents through online questionnaires. The findings reveal that both social media and micro-influencer credibility significantly impact destination awareness and tourist visit intention. Furthermore, destination awareness partially mediates the relationship between the independent variables and revisit intention. These results suggest that enhancing social media content and engaging credible micro-influencers can effectively increase tourism interest in emerging destinations like Napabhale.